Risk factors of caries in pre school children of the Peruvian Amazon - Uchima Koecklin, Karin Harumi, (2021)
Objective: To investigate the influence of sociodemographic factors and characteristics attributed to the host, substrate and potential microorganisms in risk of early childhood caries on 2-to-5 years-old infants from a rural community of the Peruvian Amazon. Methods: Cross-sectional study in 155 pre-school children between 2-5 years old, from the district of Pichanaki. A clinical examination and questionnaire were carried out. For risk analysis, univariate and multivariate logistic regression models, corrected using the Holm-Bonferroni method and a bootstrapping with 10000 sampling cycles were used. Results: The prevalence of dental caries was 83.3%. Factors associated with dental caries were a history of urinary tract infections during pregnancy (p = 0.005), poor oral hygiene (p = 0.001), sharing utensils with their main caregiver (p = 0.018), and having older siblings with cavities (p = 0.025). The univariate analysis showed that urinary tract infections during pregnancy, poor oral hygiene, sharing utensils and having older siblings with caries increased the risk of ECC. The multivariate model showed that only the poor oral hygiene (OR: 1.99, 95% CI: 1.34 – 2.96, p = 0.001) and urinary tract infections (OR: 2.98, 95% CI: 1.13 – 7.81, p = 0.027) were associated with higher risk for dental caries. Conclusions: The urinary tract infections during pregnancy and an inadequate oral hygiene are strongly predisposing factors for early childhood caries in children between 2 to 5 years old from a rural community in the Peruvian Amazon.